1996
DOI: 10.1073/pnas.93.18.9793
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility of cellular aging and neoplastic transformation: a clonal analysis.

Abstract: Prolonged incubation of NIH 3T3 cells under the growth constraint of confluence results in a persistent impairment of proliferation when the cells are subcultured at low density and a greatly increased probability of neoplastic transformation in assays for transformation. These properties, along with the large accumulation of age pigment bodies in the confluent cells, are cardinal cellular characteristics of aging in organisms and validate the system as a model of cellular aging. Two cultures labeled a and 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Our data also suggest that SSeCKS ensures contact-inhibited growth through a secondary, fail-safe function, that being an ability to scaffold residual cyclin D protein in the cytoplasm. In agreement with this, several studies have shown that continuous plating of untransformed chick embryo fibroblasts at high densities increases the frequencies of spontaneous oncogenic transformation compared to cells plated at low densities (13,14,50).…”
Section: Discussionmentioning
confidence: 49%
“…Our data also suggest that SSeCKS ensures contact-inhibited growth through a secondary, fail-safe function, that being an ability to scaffold residual cyclin D protein in the cytoplasm. In agreement with this, several studies have shown that continuous plating of untransformed chick embryo fibroblasts at high densities increases the frequencies of spontaneous oncogenic transformation compared to cells plated at low densities (13,14,50).…”
Section: Discussionmentioning
confidence: 49%
“…The impairment of growth, most apparent at low density, is a common accompaniment of transformation and apparently reflects genetic damage to the cells (3)(4)(5)31,33,34,37). By contrast, the transformed cells multiplied at the same rate as they did at low population density, although exhibiting a shorter lag period.…”
Section: Resultsmentioning
confidence: 99%
“…And if that uniqueness is not readily apparent from visual inspection, when we combine it with the heterogeneity of the reduced growth rate [26], we can say that any of an enormous number of deletions can contribute to progressive transformation if we are dealing with an already susceptible cell which can be defined as preneoplastic. Another subline derived from the same ancestral cells but with a different history of subculture will not undergo transformation under exactly the same conditions that transformed the preneoplastic cell line unless subjected to those conditions repeatedly.…”
Section: Significance For Cliniciansmentioning
confidence: 99%